1977
DOI: 10.1136/bjo.61.12.761
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus and coexisting atopic disease.

Abstract: SUMMARY The association of keratoconus and atopic disease has been reported on several occasions but the only controlled clinical study that has so far been published found no evidence to support this view. Since it is now known that atopy is often associated with changes in various immunoglobulins, particularly IgE, it was considered desirable to determine the immunological profiles of a large series of keratoconus cases in order to seek evidence for coexistence of the two conditions in one individual. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
2
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(100 citation statements)
references
References 12 publications
8
84
2
6
Order By: Relevance
“…Numerous studies suggest that this system is also activated by mechanical injury to the corneal epithelium (Wilson et al, 1996 ;Helena et al, 1998). Interestingly, previous studies have associated sources of chronic corneal epithelial injury such as eye rubbing, poorly fit contact lenses, and atopic disease of the eye with keratoconus (Coyle, 1984 ;Harrison et al, 1989 ;Koreman, 1986 ;Krachmer et al, 1984 ;Macsai et al, 1990 ;Rahi, 1977). Thus, chronic epithelial injury may link together these seemingly unrelated risk factors associated with keratoconus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies suggest that this system is also activated by mechanical injury to the corneal epithelium (Wilson et al, 1996 ;Helena et al, 1998). Interestingly, previous studies have associated sources of chronic corneal epithelial injury such as eye rubbing, poorly fit contact lenses, and atopic disease of the eye with keratoconus (Coyle, 1984 ;Harrison et al, 1989 ;Koreman, 1986 ;Krachmer et al, 1984 ;Macsai et al, 1990 ;Rahi, 1977). Thus, chronic epithelial injury may link together these seemingly unrelated risk factors associated with keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have suggested that the disease is associated with contact lens wear (Koreman, 1986 ;Macsai et al, 1990), chronic eye rubbing (Coyle, 1984), and atopy of the eye (Rahi et al, 1977 ;Harrison et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…3,12,18,79,84,85 However, the effect of atopy is controversial. 86,87 Several authors did not find a statistically significant difference between a group of control and keratoconic patients.…”
Section: Atopymentioning
confidence: 99%
“…66 Allergy and atopy have been the most commonly addressed risk factors for CHAR in KC. 79 However, a review of reports of CHAR indicated a range of other provocative factors for, or associated with, abnormal eye rubbing included dryness induced ocular irritation, psychogenesis, mental stress or emotional tension and compulsive behavior. 70 The question arises as to whether KC patients are more susceptible to adopting a CHAR that has a psychogenic basis, especially in light of reports of KC patients having unusual personality characteristics.…”
Section: Eye Rubbingmentioning
confidence: 99%
“…Among the environmental factors, frequent eye rubbing [8] and contact lenses wearing [9] are mentioned. Also, in some reports, coexistence of KTCN with atopy is presented [10][11][12]. Genetic studies have led to the identification of several loci on many chromosomes, linked to KTCN, including 1p36.23-36.21, 2p24, 2q13, 3p14-q13, 5q14.3-q21.1, 5q21.2, 5q32-q33, 9q34, 13q32, 14q11.2, 14q24.3, 15q15.1, 15q22.…”
Section: Keratoconusmentioning
confidence: 99%